Theory of automata, languages and computation - Kumar, Rajendra (New Delhi, India : Tata McGraw-Hill Publishing Company Limited, 2010)
This book on Automata, Languages and Computation provides coherent and details coverage of the Automata Theory concepts. Using simple and lucid explanations. The various features such as step-wise solved examples, graded problems, MCQs along with hints & answers to exercise questions, makes this text easier to comprehend & learn from.
1. Mathematical Preliminaries -- 2. Finite Automata -- 3. Formal Languages -- 4. Regular Languages and Regular Grammar -- 5. Properties of Regular Languages -- 6. Context Free Grammar and Context Free Language -- 7. Push Down Automata -- 8. Properties of Regular and Context Free Languages -- 9. Turing Machines -- 10. Undecidability and Computability -- 11. NP-Completeness -- Appendix -- Index.
Includes bibliographical references and index.
Keywords: MACHINE THEORY